The importance of emotional episodes in the acquisition of moral understanding - Ontiveros Llamas, Lucia (2024)
In this thesis, I will defend the view that, although moral understanding can be acquired in multiple compatible ways, instances of moral understanding correctly acquired via emotional episodes seem to stand higher in the scale of moral understanding in contrast with instances of moral understanding correctly acquired non-emotionally. In chapter I, I introduce the case of Moral Mary who has spent the first eighteen years of her life at a moral laboratory emotionally ‘sedated’. Inside the laboratory, Mary was trained to acquire as many instances of moral understanding why-p (henceforth just ‘moral understanding’) of types of action labelled as ‘right’ and ‘wrong’ as possible. The aim of the Moral Mary experiment is to show that without the experience of emotional episodes, her acquisition of moral understanding inside the laboratory is deficient. This deficiency will be made clearer throughout the subsequent chapters of the thesis. In the first section of chapter I, I develop Mary’s story, endorse Simple-K reliabilism as an analysis of knowledge (Dretske 1989), and discuss the possibility of moral knowledge for realist and some anti-realist views (Audi 2019) (Jenkins 2015). In the second section, I endorse a reductionist view of moral understanding (Sliwa 2017). In other words, I am committed to the claim that that every instance of moral understanding is constituted by some degree of moral knowledge (Ibid: 530). In the same section, I also argue that Alison Hills’ view of moral understanding as the capacity for moral reasoning fails to capture other ways in which moral understanding can be acquired (Hills 2009). Finally, in the third section I outline my account of moral understanding in light of the Moral Knowledge Account (Sliwa 2017), and elucidate the way in which it can be regarded as a kind of epistemic sentimentalism. In chapter II, I argue that moral testimony—the most common way in which moral knowledge and moral understanding can be acquired— is problematic mainly for the reason that the understanding that it provides is insufficient for acquiring the highest level of moral understanding. In the first section, I introduce the most widely accepted pessimistic theory which finds moral testimony problematic (moral pessimism) (Nickel 2001, Hills 2009, McGrath 2011, 2019), but mainly focus on describing Guy Fletcher’s view (Fletcher 2016). Fletcher has argued that moral testimony is problematic due to the fact that moral sentiments—which are intimately related to moral judgements—are at least difficult to form on the basis of pure, direct, testimony. In the same section I also describe Laura Callahan’s Affect and Motivation view, which aims to provide novel reasons to hold moral pessimism (Callahan 2018). In the second section, I elucidate Daniel Wodak’s optimistic argument for approving on the basis of moral and aesthetic testimony, in order to criticise Fletcher’s pessimism, as well as moral pessimism (Wodak 2019). Thirdly, whilst I agree with Wodak’s claim that deferring to the moral testimony of others can provide us with reasons to morally approve or disapprove, I challenge his optimism by arguing that having reasons to approve or disapprove is not sufficient for possessing the highest degree of moral understanding. In chapter III, my aim is to argue is that, unless they misfire, emotions can play a positive epistemic role. By ‘epistemic role’ I am referring to the production or modification of justified true belief and understanding. Concretely, I will defend the claim that emotions can be sources of salience (e.g., de Sousa 1987; Hookway 2008; Elgin 1996, 2008; Ben-Ze’ev 2010). In other words, emotions sometimes direct our attention to certain aspects of a given situation (e.g., when she encounters them, Mary’s fear of spiders makes certain features of spiders salient, as well as the ways in which she can get rid of the spiders). In the first section of this chapter, I elucidate the theory of emotions that I will be assuming throughout the thesis, and which falls under the category ‘hybrid evaluative-feeling’ (de Sousa and Scarantino 2021). In the second section, I describe in detail the ways in which emotions can play different putative and positive epistemic roles, and present some objections to these claims (Elgin 2008). In the third section, I discuss the Perceptual Theory of Emotions and the fact that when emotions act like perceptual experiences, the content that they provide is non-conceptual (Tappolet 2016). Finally, in the fourth section I discuss some ways in which emotions can be misleading (Goldie 2008) and irrational (e.g., Brady 2007, 2009). In chapter IV, my aim is to argue that attention is a necessary condition to acquire understanding in general. I intend to defend this claim, to show that, since emotional episodes can in some cases focus our attention on the morally relevant features of certain actions, emotional episodes can lead to the acquisition of moral understanding. In the first section, I will first provide the definition of attention that I will be assuming throughout the rest of the thesis, and discuss how attention relates to consciousness (i.e., self-awareness) (Brentano 1874). Secondly, I will describe four features of attention (selectivity, clarity, phenomenal character, controllability), in order to later focus on the importance that selectivity and clarity bear on the acquisition of understanding. Thirdly, I will outline how the involuntariness of attention (James 1890) will be relevant for showing that it is possible to acquire understanding without making an explicit effort to do so. In the second section, I will first provide a brief historical account of some positive epistemic roles attributed to attention to support the claim that understanding requires attention. Secondly, I will argue that given the selectivity and clarity that it provides, attention is necessary for the acquisition of understanding. In the third section, I will first elucidate the way in which it has been argued that emotions can direct attention, since this mechanism will be crucial to describe the roles that some moral emotions can play in chapters V and VI. Secondly, I will also argue that although desires are mental states that in principle can also direct our attention (Schroeder 2007) and increase our understanding, the fact that emotions always involve a feeling component makes them better candidates to explain the acquisition of at least two instances of moral understanding that I have in mind. In chapter V, my aim is to argue that the highest level of moral understanding necessarily requires an emotional acquaintance with morally appraised actions. In the first section, I will begin by elucidating the view that moral understanding comes in degrees (Hills 2009: 103) (Sliwa 2017: 537, 548). I will also do this by referring back to the case of Moral Mary, and by describing what would constitute the different levels of the different putative instances of moral understanding. Secondly, I will point out that it is possible to acquire understanding of morally appraised actions in multiple compatible ways (e.g., via testimony, moral reasoning, emotional experiences, performing prima facie moral actions, via imaginings, epiphanies, contemplation of a work of art, etc.). Thirdly, I will emphasise that a thorough account of moral understanding should consider upstream (i.e., non-practical), downstream (i.e., practical) and combined (i.e., both practical and non-practical) instances of moral understanding. In the third section, I will describe what virtuous emotional acquaintance consists in. I will understand virtue as the ability to ‘…recognize requirements which situations impose on one's behaviour’ (McDowell 1979: 333), and rely on the Aristotelian model of the emotionally virtuous agent (NE, II, V: 1106b). Given that the emotionally virtuous agent experiences emotions ‘…at the right times, with reference to the right objects, towards the right people, with the right motive, and in the right way’ virtue will be necessary for acquiring correct moral understanding of putative moral actions (Ibid: 1106b). Besides the valuable upstream and downstream moral understanding that emotions can allow us to gain due to their components, virtuous emotion is also epistemically privileged given the perceptual awareness that comes with it (Starkey 2008: 425). I will then describe the perceptual awareness of virtuous emotion, and argue that putatively moral actions are understood to their highest degree by emotional acquaintance (e.g., Mary fully understands the wrongness of lying once she experiences different episodes of guilt related to lying). Finally, in chapter VI, I will argue that in some cases, certain emotional episodes can change—and thereby improve—our moral perspectives, and even our moral behaviour. By ‘moral perspective’, I am referring to the epistemic standpoint whereby agents identify the morally salient features that ground the set of general moral beliefs that they implicitly endorse (e.g., ‘acts of charity are right’, ‘lying to your friends is wrong’). I argue that, since typically moral emotions (e.g., compassion and guilt) make certain features of moral actions striking or salient, their experiencing them can direct our attention to new or different morally relevant features, thereby producing a change in moral perspectives, which in turn can involve an improvement in our moral behaviour. Firstly, I briefly introduce some views that define certain emotions as moral (Gibbard 1990) (Haidt 2003). I intend to argue that a certain experience of typically moral emotions can involve a change in moral perspectives, given that these emotional episodes can constitute, arise from, or are associated to moral judgements (Prinz and Nichols 2010:112). Thirdly, through some examples, I argue that a shift in our second-order moral views —i.e., those views and/or attitudes about the appropriate grounds of moral judgements (Sinclair 2021:194)—brought about by an emotional episode can lead to a change in moral perspectives. I will argue that even though inside the moral laboratory, Moral Mary possesses a high degree of moral understanding (e.g., it could even be argued that she possesses the six reasoning abilities involved in Hills’ account of moral understanding to the greatest extent), she still lacks the information and evaluation provided by emotional episodes. I argue that she would also lack the distinctive motivation and feeling experience that they can cause, which in turn can all contribute to an increase in understanding of morally appraised types of action. I argue that these components, together with the attentional focus on the prima facie morally relevant aspects of an action or a situation that can be provided by emotions show the importance of emotional episodes in the acquisition of moral understanding. I also argued that virtuous emotional acquaintance with various morally appraised types of action consists in part in the highest level of moral understanding, and that some emotional episodes can lead to a change in moral perspectives. My Moral Epistemic Sentimentalism (MES) describes emotions in a positive epistemic light, but it is also cautious, as it acknowledges and discusses the ways in which emotions can misfire or hinder our acquisition of understanding in general.